2022
DOI: 10.1038/s41419-022-04877-8
|View full text |Cite
|
Sign up to set email alerts
|

UHMK1 aids colorectal cancer cell proliferation and chemoresistance through augmenting IL-6/STAT3 signaling

Abstract: UHMK1, a serine/threonine kinase with a U2AF homology motif, is implicated in RNA processing and protein phosphorylation. Increasing evidence has indicated its involvement in tumorigenesis. However, it remains to be elucidated whether UHMK1 plays a role in the development of colorectal cancer (CRC). Here, we demonstrated that UHMK1 was frequently upregulated in CRC samples compared with adjacent normal tissue and high expression of UHMK1 predicted poor outcomes. Knockdown of UHMK1 by siRNAs restrained CRC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…UHMK1 has been implicated as an attractive therapeutic target by exerting its potent oncogenic functions in different ways in many types of cancer. 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 40 This motivated us to explore the role and possible mechanism of action of UHMK1 in LUAD. In our study, we identified UHMK1 as significantly overexpressed in LUAD patients, leading to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…UHMK1 has been implicated as an attractive therapeutic target by exerting its potent oncogenic functions in different ways in many types of cancer. 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 40 This motivated us to explore the role and possible mechanism of action of UHMK1 in LUAD. In our study, we identified UHMK1 as significantly overexpressed in LUAD patients, leading to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 , 43 Under certain conditions, autophagy contributes to cell survival and improves the tolerance to drug therapy. 44 , 45 Interestingly, some studies have indicated that UHMK1 can mediate oxaliplatin, 28 5‐fluorouracil 46 resistance in colorectal cancer, and vemurafenib resistance in melanoma. 22 Our findings might provide insights into UHMK1‐mediated drug resistance in tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations